2006
DOI: 10.1007/s11010-005-9017-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effects of cadmium on rat liver

Abstract: Cadmium is one of the most toxic pollutants in environment. Cadmium accumulation in blood affects the renal cortex and causes renal failure. In this study, we aimed to evaluate the effects of cadmium on rat liver tissue. Eighteen male albino rats aged ten weeks old were used in the study. 15 ppm of cadmium was administered to rats via consumption water daily. At the end of the 30th study day, the animals were killed under ether anesthesia. After the liver tissue samples were taken, histopathological and bioche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
62
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(71 citation statements)
references
References 24 publications
7
62
1
1
Order By: Relevance
“…Histopathology of the major organs involved in metabolism and excretion of xenobiotics, as the liver, are useful biomarkers of the effects of pollution (Koyu et al, 2006). Several studies have reported that oxidative stress plays a central role in disease pathogenesis and in tissue damage in response to toxicant exposures (Roberts et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Histopathology of the major organs involved in metabolism and excretion of xenobiotics, as the liver, are useful biomarkers of the effects of pollution (Koyu et al, 2006). Several studies have reported that oxidative stress plays a central role in disease pathogenesis and in tissue damage in response to toxicant exposures (Roberts et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that oxidative stress plays a central role in disease pathogenesis and in tissue damage in response to toxicant exposures (Roberts et al, 2009). For example, Koyu et al (2006) showed that cadmium has an important toxic effect on liver tissue and concluded that cadmium exhibits its toxicity by increasing lipid peroxidation. Tabrez and Ahmad (2009) evaluated antioxidant enzymes and MDA levels of rats treated with polluted water collected from industrial regions of the urban area of India.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reactions of Cd with GSH may lead to either the formation of complexes [51] or the oxidation of GSH. Cd induces oxidative stress also by decreasing the activities of some antioxidant enzymes in the liver such as SOD, CAT and GPx [50,[52][53][54], which play an important role in the elimination of free radicals. SOD, which converts O 2…”
Section: Sulfhydryl Group Inactivation and Oxidative Stressmentioning
confidence: 99%
“…Several studies demonstrate a relationship between Cd exposure and LPO [52,54,70,71] showing that Cd increased the hepatic level of malondialdehyde (MDA). Cd, through binding to the inner membrane, enhances LPO and disturbs the integrity of mitochondrial membranes.…”
Section: Mitochondria and Cadmiummentioning
confidence: 99%